1990
DOI: 10.1080/15287399009531402
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology and carcinogenesis studies of dietary titanium dioxide‐coated mica in male and female Fischer 344 rats

Abstract: Male and female Fischer 344 rats were fed diets containing 0, 1.0, 2.0, or 5.0% titanium dioxide (TiO2) coated mica for up to 130 wk. This dosage regimen produced no consistent or biologically important changes in survival, body weight gains, hematologic or clinical chemistry parameters or histopathology. Under the conditions of this 130 wk feeding study there was no evidence that TiO2-coated mica produced either toxicologic or carcinogenic effects at dietary concentrations as high as 5.0%. The results suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(50 citation statements)
references
References 16 publications
1
46
0
Order By: Relevance
“…Micro-sized titanium dioxide is suggested to be biologically inert (11,12), although an inflammatory response has been described (10). Particles can generate reactive oxygen species; particularly in the case of nano-sized particles, DNA adducts are observed in human lung cells (9,13).…”
Section: Induction Of Altered Mrna Expression Profiles Caused By Fibrmentioning
confidence: 99%
“…Micro-sized titanium dioxide is suggested to be biologically inert (11,12), although an inflammatory response has been described (10). Particles can generate reactive oxygen species; particularly in the case of nano-sized particles, DNA adducts are observed in human lung cells (9,13).…”
Section: Induction Of Altered Mrna Expression Profiles Caused By Fibrmentioning
confidence: 99%
“…The photocatalytic effect of TiO 2 has been applied to cancer treatment [20][21][22][23][24][25], and US irradiation is an alternative energy source for TiO 2 [26][27][28]. Furthermore, toxicological examinations have shown that the TiO 2 nanoparticle is basically nontoxic for experimental cells or animals [29][30][31]. Therefore, we supposed that sonocatalytic TiO 2 could become a new material in SDT for various cancers involving malignant glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) has been increasingly employed in a variety of industrial applications including production of paper, plastics, cosmetics, and paints (Wang et al 2007) and TiO 2 micro-and nanoparticles were classifi ed as comparatively inert (Chen and Fayerweather 1988;Bernard et al 1990;Hart and Hesterberg 1998). These ubiquitous applications lead to increasing human exposure to these nanoparticles.…”
Section: Introductionmentioning
confidence: 99%